Percutaneous Needle Tenotomy for the Treatment of Lateral Epicondylitis: A Systematic Review of the Literature. Issue 6 (22nd October 2016) - Mattie, Ryan; Wong, Joseph; McCormick, Zachary; Yu, Sloane; Saltychev, Mikhail; Laimi, Katri
Abstract: Objective: To analyze the literature to determine whether controlled studies on percutaneous tenotomy have been published, and if so, to systematically assess the efficacy of percutaneous tenotomy for the treatment of tendinosis at the lateral epicondyle of the elbow. Design: Systematic review of the available literature. Methods: Cochrane Controlled Trials Register (CENTRAL), MEDLINE, EMBASE, CINAHL, and Web of Science databases were searched in November 2015, unrestricted by date. After the initial search, we excluded conference proceedings, theses, reviews, expert opinions, and publications written in languages other than English. Next, 2 independent reviewers screened all of the remaining records with regard to their titles and abstracts, and subsequently, the full texts of identified publications potentially relevant to the present study. Results: Six articles focused on percutaneous tenotomy, none of which were controlled against a placebo or conservative treatment group. The absence of true randomized controlled trials created a great deal of heterogeneity between the studies; thus we could not include any of our studies in the intended final quantitative analysis with meta‐analysis tools. We describe all 6 studies identified by this systematic review with a detailed analysis of the procedural methods, outcome measures, and conclusions of each study. Conclusions: Percutaneous tenotomy presents an alternative to surgical release of the common extensor tendon for the treatment of chronic tendinosis at the lateral epicondyle of the elbow. Current research supporting the efficacy of this procedure, however, is of low quality (level II to level IV). Level of Evidence: III